Length and pressure matter: Expediting evidence‐based progress in femoropoliteal intervention. Issue 7 (1st June 2017) - Chatterjee, Arka; Hillegass, William B.
Key Points: Preprocedural lesion length and ankle‐brachial indices (ABI) synergistically predict 12‐month patency and repeat revacularization in claudicants treated with bare metal nitinol stents for femoropopliteal disease. This predictive length‐ABI model will permit broader evidence‐based indirect comparisons of newer femoropopliteal approaches such as drug eluting balloon treatment with or without atherectomy. The length‐ABI model is a step to supplement and supplant randomized controlled trials with indirect comparisons as the necessary evidence source expediting innovation and optimizing personalized endovascular therapy for infrainguinal obstructive peripheral arterial disease.